The work to inscribe ourselves in history: memories of a young student activist in the Uruguayan dictatorship (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
Memory gaps regarding the experience of young people under State terrorism are forms of impunity that affect the entire society and prevent understanding of what made these levels of violence possible. In the case of social memories about the last dictatorship in Uruguay, the dominant narratives have adults as main characters and are also constructed by adults, giving priority to the testimonies of men. This monotonous tone of hegemonic memory leaves out much of the experience that would help explore other possible narratives beyond war imaginaries. The incorporation of new subjects in the constructions of the social memory of the dictatorship in Uruguay, such as women and young people, responds to a new context of reception and forms of organization that allow us to try to give new meanings to the past, transforming private memories into collective memories. In this paper, we explore the case of a young student activist who introduces new actors, events and circumstances that allow the dismantling of discourses that sustain impunity.